Deconstructing Adaptive Management: Criteria for Applications to Envir onmental Management - Gregory, R.; Ohlson, D.; Arvai, J. (Ecological Applications, 2006)
[The concept of adaptive management has, for many ecologists, become a foundation of effective environmental management for initiatives char acterized by high levels of ecological uncertainty. Yet problems assoc iated with its application are legendary, and many of the initiatives promoted as examples of adaptive management appear to lack essential c haracteristics of the approach. In this paper we propose explicit crit eria for helping managers and decision makers to determine the appropr iateness of either passive or active adaptive-management strategies as a response to ecological uncertainty in environmental management. Fou r categories of criteria–dealing with spatial and temporal scale, dime nsions of uncertainty, the evaluation of costs and benefits, and insti tutional and stakeholder support–are defined and applied using hypothe tical yet realistic case-study scenarios that illustrate a range of en vironmental management problems. We conclude that many of the issues f acing adaptive management may have less to do with the approach itself than with the indiscriminate choice of contexts within which it is no w applied.]